Elution of antibiotics from bone cement: problems and ways to solution - Shafigulin, R. A.; Akhtyamov, I. F.; Emelin, A. L.; Bespalov, I. A.; Akifyev, K. N. (Geniĭ ortopedii = Genij ortopedii, 2025)
Introduction The widespread use of bone cement in the treatment of patients with orthopedic infections can be associated with limited elution of antibiotics with use of local spacers. The objective was to determine problems of elution of antibiotics from bone cement and ways to solve them based on literature data. Material and methods The original literature search was conducted on key resources including Scientific Electronic Library (www.elibrary.ru) and the National Library of Medicine (www.pubmed.org) (1994 to 2024) and using keywords: bone cement, PMMA, polymethylmethacrylate, antibiotic elution, bone cement, antibiotic elution, additive manufacturing, porous constructions, lattice structures. The sources were included based on the hypothesis that preformed implants based on a lattice structure could be used in combinations with bone cement. Results and discussion The elution of antibiotics from bone cement can be improved through examination of the cement type, the porosity, the implant/spacer shape, the type of antibiotics, quantities and  combinations administered that pose a difficult scientific problem in the absence of an acceptable solution along with the variety of publications. However, research in this area has not led to any complete solution. Conclusion A paradigm has been developed for improving the elution of antibiotics from polymethyl methacrylate (PMMA) to include working with the cement: its composition, geometry and pyrogenicity. Solutions offered for improving the elution of antibiotics from PMMA are often impracticable and can deteriorate the performance properties of cement. Another approach can involve a research aimed at studying the effectiveness of spacers with a preformed base and bone cement coating, without or with minimal interference with the properties specified by the manufacturer.